2019
DOI: 10.1108/ajems-10-2018-0299
|View full text |Cite
|
Sign up to set email alerts
|

Inflation shocks and income inequality

Abstract: Purpose The purpose of this paper is to analyze the effects of inflationary shocks on inequality, using data of selected countries of the Middle East and North Africa (MENA). Design/methodology/approach Inflationary shocks were measured as deviations from core inflation, based on a genetic algorithm. Bayesian quantile regression was used to estimate the impact of inflationary shocks in different levels of inequality. Findings The results showed that inflationary shocks substantially affect countries with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Also Yolanda (2017) found that the effect of inflation on poverty was significant and positive. Gonzales and Rojas-Hosse (2019) show that inflation shocks substantially affect countries that experience higher levels of income inequality, thereby suggesting that the adverse effects of inflation are exacerbated by high levels Avalaible online at http://journals.ums.ac.id, Permalink/DOI: 10.23917/jep.v21i2. 11254 Jones production function, namely the increase in population caused by the production function for consumer goods and the production function for children.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331 137mentioning
confidence: 99%
“…Also Yolanda (2017) found that the effect of inflation on poverty was significant and positive. Gonzales and Rojas-Hosse (2019) show that inflation shocks substantially affect countries that experience higher levels of income inequality, thereby suggesting that the adverse effects of inflation are exacerbated by high levels Avalaible online at http://journals.ums.ac.id, Permalink/DOI: 10.23917/jep.v21i2. 11254 Jones production function, namely the increase in population caused by the production function for consumer goods and the production function for children.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331 137mentioning
confidence: 99%